Inhibition of lipopolysaccharide-induced nitric oxide and prostaglandin E2 production by chloroform fraction of Cudrania tricuspidata in RAW 264.7 macrophages - Yang Gabsik; Lee Kyungjin; Lee Mihwa; Ham Inhye; Choi Ho-Young (BMC, 2012)
Abstract Background Cudrania tricuspidata extract is an important traditional herbal remedy for tumors, inflammation, gastritis, and liver damage and is predominantly used in Korea, China, and Japan. However, the anti-inflammatory effects of the extract have not yet been conclusively proved. Methods In this study, we investigated the effects of the CHCl3 fraction (CTC) of a methanol extract of C. tricuspidata on the lipopolysaccharide (LPS)-induced nitric oxide (NO) and prostaglandin E2 (PGE2) production in RAW 264.7 macrophage cells and mouse peritoneal macrophages, and the levels of pro-inflammatory cytokines tumor necrosis factor-α (TNF-α), interleukin (IL)-1β and IL-6 in RAW 264.7 macrophage cells. Results We observed that the protein expression levels of inducible NO synthase and COX-2 enzymes were markedly inhibited by CTC in a concentration-dependent manner. In addition, CTC reduced the production of TNF-α, IL-1β, and IL-6 in the LPS-stimulated RAW 264.7 macrophage cells. Conclusions Our results show that the C. tricuspidata extract could modulate macrophage-mediated inflammatory functions such as the overproduction of cytokines, NO, and PGE2. The CTC was found to be the active fraction in this context.